IMPLEMENTASI PENANAMAN KARAKTER SHOLEH, ILMUWAN, DAN PEMIMPIN SEBAGAI CIRI KHAS KARAKTER LULUSAN - Darmanto, Darmanto (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2019)
The research aims to determine the implementation of SIP (sholeh, ilmuwan, peminpin) charater instilling as a characteristic of characters building at SDIT Alam Nurul Islam Dua Ngawi. The research was a qualitative study with case study research. This research used purposive technique with the subject consisted of the third to fifth grade, and SIP teacher, and informant were the vice principals, assistens principil for student, and the expert teacher specially for the character builder (SIP Teacher). The data collected by observation, documentation, and interview. The research?s result show that the instilling of SIP character can also be done proactively through the development of Islamic culture in school. The development of islamic culture in school must be carried out continuously by school comunity so that the detemined character can be achieved properly. The development of islamic school culture is know as the SIP culture (sholeh, scientist, and leaders) wich is made as a characteristic of the caracter building at SDIT Alam Nurul Islam Dua Ngawi. The implementation of SIP character instilling at SDIT Alam Nurul Islam Dua Ngawi is carried out through continuously activity such as prayer congrecationally in mosque, memorizing holy qur?an, reciting and writing holy qur?an, memorizing selected hadits, reciting Al Ma?surat, marketday, islamic scouting, pencak silat, outbond, outing class, gardening, farming, spontaneous activity example reward or punishmen etc.